Efektivitas Video Animasi terhadap Peningkatan Pengetahuan tentang HIV/AIDS - Nurdianti, Reni; Rahmawati, Ai; Nuryani, Windanesti Dwi (Universitas Malahayati, 2023)
ABSTRACT HIV/AIDS is the biggest health problem in almost the whole world. Lack of information about HIV AIDS in adolescents can lead to promiscuity which leads to the transmission of the infectious disease HIV/AIDS, so it is necessary to provide information to help adolescents understand and realize how dangerous HIV/AIDS is. To determine the effectiveness of animated videos on increasing knowledge about HIV AIDS among students at SMAN 3 Kota Tasikmalaya. Used a quantitative research design with a quasy experiment one group pretest post test design. The sample in this study were 273 students of SMAN 3 Kota Tasikmalaya. Data were obtained using a questionnaire and analyzed using the Wilcoxon test. The results showed that there was an effect of the effectiveness of anisami video on increasing knowledge about HIV AIDS in students of SMAN 3 Tasikmalaya City with a p-value of 0.000 <0.05. The conclusion of this study is that there is an effect of the effectiveness of animated videos on increasing knowledge about HIV AIDS in students of SMAN 3 Tasikmalaya City, therefore, it is hoped that this can be used as an alternative choice of health education media to provide information in conveying education about adolescent sex. Keywords: HIV AIDS, Knowledge, Animated Videos ABSTRAK HIV/AIDS merupakan masalah kesehatan terbesar yang terdapat hampir di seluruh dunia. Kurangnya informasi tentang HIV AIDS pada remaja dapat menjerumuskan pada pergaulan bebas yang mengarah terhadap penularan penyakit menular HIV/AIDS, sehingga perlu dilakukan pemberian informasi untuk membantu agar remaja memahami dan menyadari seberapa berbahayanya HIV/AIDS. Untuk mengetahui efektivitas video animasi terhadap peningkatan pengetahuan tentang HIV AIDS pada siswa SMAN 3 Kota Tasikmalaya. Penelitian ini menggunakan kuantitatif dengan desain penelitian quasy eksperiment one group pretest post test desain. Sampel dalam penelitian ini yaitu siswa SMAN 3 Kota Tasikmalaya sebanyak 273 orang siswa. Data diperoleh dengan menggunakan kuesioner dan dianalisis menggunakan uji Wilcoxon. Penelitian menunjukkan adanya pengaruh efektivitas video anisami terhadap peningkatan pengetahuan tentang HIV AIDS pada siswa SMAN 3 Kota Tasikmalaya dengan p-value 0,000<0,05. Penelitian ini yaitu terdapat pengaruh efektivitas video animasi terhadap peningkatan pengetahuan tentang HIV AIDS pada siswa SMAN 3 Kota Tasikmalaya, oleh karena itu, diharapkan dapat dijadikan pilihan alternatif media edukasi kesehatan untuk pemberian informasi dalam menyampaikan edukasi tentang seks remaja. Kata Kunci : HIV/AIDS, Pengetahuan, Video Animasi